The Biotechnological Potential of Pediococcus spp. Isolated from Kombucha Microbial Consortium - Camelia Filofteia Diguță; George Daniel Nițoi; Florentina Matei; Gabriela Luță; Călina Petruța Cornea (Foods, 2020)
In the past decade, the probiotic market has grown rapidly, both for foods and supplements intended to enhance wellness in healthy individuals. Different lactic acid bacteria (LAB), especially Lactobacillus spp., of different origins have already been used to develop commercial probiotic products. Nowadays, LAB new alternative sources, such as non-dairy fermented food products, are being exploited. One such source is Kombucha, a fermented low-alcohol beverage made of tea leaves. In this regard, we tested seven Pediococcus spp. strains isolated from a local industrial Kombucha for their biotechnological potential. Two, out of the seven isolates, identified as Pediococcus pentosaceus (L3) and Pediococcus acidiliactici (L5), were selected as successful candidates for the food industry, due to their probiotic and technological properties. In regard to their resistance in the gastro-intestinal tract, both selected strains were tolerant to a pH of 3.5, presence of 0.3% pepsin, and 0.5% bile salt concentration. On the antagonistic side, the fresh suspension of selected isolates had high inhibitory activity against pathogenic bacteria, such as Salmonella enterica Typhimurium, Listeria monocytogenes, Listeria ivanovii, Bacillus cereus, Proteus hauseri, and methicillin resistant Staphylococcus aureus. In addition, moderate to high inhibitory activity was noticed against foodborne molds (e.g., Penicillium expansum and Penicillium digitatum). These safety issues were supported by their negative hemolytic activity and good antioxidant potential (56–58%). Selected isolates were sensitive to ampicillin, penicillin, erythromycin, and lincomycin, while a broad range of other antibiotics were not effective inhibitors. On the technological side, both strains tolerated 5% NaCl and, during the freeze-drying process, had a good survival rate (86–92%). The selected Pediococcus strains have proven properties to be used for further development of functional products.